The Influence of AI-Chatbot Service Quality and Customer Trust on Brand Image among Shopee Users in Indonesia - Vita Asyrifah; Popy Rufaidah (Media Ekonomi dan Manajemen, 2026)
This research focuses on how AI chatbot service quality and costumer trust influence brand image in e-commerce platforms in Indonesia. It’s important to understand how human-like interactions and the resulting trust influence user perceptions, as chatbots become the primary interface for costumer interaction. Therefore, this research was conducted with the aim to assess how service quality, together with costumer trust, shape the way users perceive in e-commerce brand. The method used in this research is a quantitative survey of active users on one of the largest e-commerce company in Indonesia, along with a literature review to provide the basis for this topic and build theoretical framework. In this research, chatbot service quality measured in five key dimensions, including semantic understanding, human-AI collaboration, human interaction, personalization, and the efficiency of operational. Meanwhile, customer trust was evaluated in two key dimensions, such as trust in the seller and trust in the product that seller offers. Research has shown that both chatbot service quality and customer trust significantly had a positive effect on brand image, while customer trust having a stronger impact. These two variables has significantly contributed to shaping users’ perceptions towards brand image. These findings highlight the importance of providing a seamless and engaging digital experience to achieve a competitive advantage in online market.